In situ plasmonic Ag nanoparticle anchored TiO2 nanotube arrays as visible-light-driven photocatalysts for enhanced water splitting. Issue 9 (16th February 2016) - Ge, Ming-Zheng; Cao, Chun-Yan; Li, Shu-Hui; Tang, Yu-Xin; Wang, Lu-Ning; Qi, Ning; Huang, Jian-Ying; Zhang, Ke-Qin; Al-Deyab, S. S.; Lai, Yue-Kun
Abstract : An ultrasonication-assisted in situ deposition strategy was developed to realize uniform Ag nanoparticles dispersed on TiO2 nanotube arrays (Ag@TiO2 NTAs). Abstract : An ultrasonication-assisted in situ deposition strategy was utilised to uniformly decorate plasmonic Ag nanoparticles on vertically aligned TiO2 nanotube arrays (NTAs) to construct a Ag@TiO2 NTA composite. The Ag nanoparticles act as efficient surface plasmon resonance (SPR) photosensitizers to drive photocatalytic water splitting under visible light irradiation. The Ag nanoparticles were uniformly deposited on the surface and inside the highly oriented TiO2 nanotubes. The visible-light-driven hydrogen production activities of silver nanoparticle anchored TiO2 nanotube array photocatalysts were evaluated using methanol as a sacrificial reagent in water under a 500 W Xe lamp with a UV light cutoff filter ( λ ≥ 420 nm). It was found that the hydrogen production rate of the Ag@TiO2 NTAs prepared with ultrasonication-assisted deposition for 5 min was approximately 15 times higher than that of its pristine TiO2 NTAs counterpart. The highly efficient photocatalytic hydrogen evolution is attributed to the SPR effect of Ag for enhanced visible light absorption and boosting the photogenerated electron–hole separation/transfer. This strategy is promising for the design and construction of high efficiency TiO2 based photocatalysts for solar energy conversion.